Perancangan Charge Controller Untuk Pengisian Baterai Pada Sel Surya - Ahmad P Sardju; Muhammad Yunus H Abbas (Fakultas Teknik Universitas Khairun, 2021)
Good battery performance, will support the device used. The energy that a battery can store is limited, so the battery will experience charge and discharge cycles. The process of charging and discharging improperly can cause battery performance to decrease. Therefore, battery management is needed so that battery performance can reach the maximum. One aspect of battery management is monitoring the state of charge which is the ratio of the capacitance of available energy to the maximum energy capacity.In this research, a charge controller device is made whose function is to regulate the charging voltage from the solar panel to the battery so that overcharging and overvoltage do not occur and also regulate the use of the voltage from the load battery, so as not to exceed the minimum limit of battery capacity usageThe system consists of a Solar Panel, Arduino Uno R3 Microcontroller, 16x2 LCD, Relay Circuit, Buck Boost Converter Circuit, Voltage Sensor and Battery. When charging the battery reaches a voltage level of 14 volts, the relay circuit is disconnected indicating the battery is full, when the battery voltage drops to 11 volts, the relay is connected again and the battery is recharged again.